The Influence of Financial Literacy, Self-Control and Parents's Socio Economic Status on Students Consumptive Behavior - Putri, Rahmatia Eka; Sutieman, Entar; Noy, Ismail R; Marihi, La Ode; Pattiasina, Victor (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2022)
This study was conducted to examine the effect of the variables Influence of financial literacy, self control and parents' socio economic status on the consumptive behavior of Korean Pop (K-Pop) fan students in Jayapura City. The population of this study were students who were fans of k-pop music in the city of Jayapura who followed the Army_Jayapura Instagram as many as 207 people. Based on the purposive sampling technique, a sample of 104 people was obtained. This study uses descriptive quantitative methods obtained from distributing questionnaires through google form. The analysis technique used is multiple linear regression. The results of the study show that: (1) Financial literacy has a significant effect on consumptive behavior. (2) Self control has a significant effect on consumptive behavior. (3) Parents' socio economic status has no effect on consumptive behavior. (4) Financial literacy, self control and socio economic status of parents have a significant simultaneous effect on consumptive behavior in Korean Pop (K-Pop) music fan students in Jayapura City.